The Effect of Compensation and Working Environment to Job Satisfaction Employee Department of Revenue, Finance Management and Asset Soppeng Regency - Ikhwanuddin Hatang; mattalatta - (Jurnal Mirai Management, 2016)
ABSTRACT This study aims to identify and analyze the Compensation and Working Environment Influence on Job Satisfaction employee Department of Revenue, Finance and Asset Soppeng Regency either partially or simultaneously.This study will be conducted at the Department of Revenue, Finance and Asset Soppeng Regency, with a total population of 142 people. The technique of determining the number of samples in this study is based on a formula slovin so that the number of 59 employees. For testing the hypothesis with multiple regression analysis. The results showed that 1) Compensation has positive and significant impact on job satisfaction employee Department of Revenue, Finance and Asset Soppeng Regency. 2) Work Environment has positive and significant impact on job satisfaction employee Department of Revenue, Finance and Asset Soppeng Regency. 3) Compensation and Working Environment have positive and significant impact on job satisfaction employee Department of Revenue, Finance and Asset Soppeng Regency. Keywords: Compensation, Work Environment, Job Satisfaction